Sample preservation and plant sex prediction in white guinea yam (Dioscorea rotundata Poir.) - Agre, P.; Nwachukwu, C.; Olasanmi, B.; Obidiegwu, J.; Nwachukwu, E.; Adebola, P.O.; Koeyer, D. de; Asrat, A. (Applied Biotechnology Research Center, 2020)
Introduction: Yam (Dioscorea spp.) is an economically important staple food in tropical regions, especially for people in West Africa. Understanding of the flowering behavior of the crop to determine potential manipulation available to accomplish crop improvement at early stage remain key challenge in the yam breeding. The methods that reliably yield quality DNA and distinguishing sex type at the early stage of growth have been a challenge in yam genetics and breeding studies. This study assessed the effect of sample preservation methods on DNA quantity and quality during extraction and potential of DNA marker to diagnose plant sex at the early seedling stage in white Guinea yam. Materials and Methods: Five sample preservation methods were assessed for quality DNA extraction during field leaf tissue collection, namely liquid nitrogen, dry ice, silica gel, 95% ethanol, and oven drying. The predicted sex at the seedling stage using the molecular marker was further validated with the visual score for the sex phenotype at the flowering stage. Results: According to the findings of the present study, the DNA extracted from leaf samples preserved in liquid nitrogen, silica gel, dry ice, and oven drying methods were higher in molecular weights than samples stored in ethanol solution. Yam plant sex diagnosis with the DNA marker (sp16) identified a higher proportion of ZW genotypes (female or monoecious phenotypes) than the ZZ genotypes (male phenotypes) in the studied materials with 74% prediction accuracy. Conclusions: The results from this study provided valuable insights on suitable sample preservation methods for quality DNA extraction and the potential of DNA marker sp16 to predict sex in white Guinea yam.